1971
DOI: 10.1080/14640747108400242
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Visual Texture Density Gradients on Relative Distance Judgements

Abstract: A hypothesis derived from J. J. Gibson's psychophysical theory of space perception was tested. Subjects made monocular relative distance judgements by moving n marker to the apparent physical mid-point between two other fixed markers which were placed on a surface along the subjects' line of sight. Judgements were significantly influenced by the texture density gradients of stimulation derived from the surface over which they were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Thus, Gogel (1964) and Teghtsoonian and Teghtsoonian (1969) report values less than unity.Tand this conclusion is implicit in data reported by Gilinsky (1951), Harway (1963), . On the other hand, Galanter and Galanter (1973) and Teghtsoonian and Teghtsoonian (1970) report mean exponents greater than unity, and the same result is implied by data reported by Gruber (1954), Newman (1971), Purdy and Gibson (1955), Wohlwill (1963Wohlwill ( , 1964, and Whitehouse and Gruber (Note 2). These inconsistencies are not surprising in the light of the heterogeneity in the conditions of the various experiments.…”
supporting
confidence: 75%
“…Thus, Gogel (1964) and Teghtsoonian and Teghtsoonian (1969) report values less than unity.Tand this conclusion is implicit in data reported by Gilinsky (1951), Harway (1963), . On the other hand, Galanter and Galanter (1973) and Teghtsoonian and Teghtsoonian (1970) report mean exponents greater than unity, and the same result is implied by data reported by Gruber (1954), Newman (1971), Purdy and Gibson (1955), Wohlwill (1963Wohlwill ( , 1964, and Whitehouse and Gruber (Note 2). These inconsistencies are not surprising in the light of the heterogeneity in the conditions of the various experiments.…”
supporting
confidence: 75%
“…Differences in number of textural units, their shape, absolute size and spacing, and area of the retina involved have also been found to influence slant judgments (Eriksson, 1964;Gruber & Clark, 1956;Phillips, 1970). Newman (1971) found that relative distance judgments of the midpoint of a surface differed with varying numbers of elements in the texture, and Wohlwill (1962) reported similar findings using textures to suggest depth in pictures. All these results indicate that, despite entirely constant gradients of texture density, variations in several specifiable properties of surface texture influenced judgments of slant and distance.…”
mentioning
confidence: 57%
“…Such cues have been studied by presenting the subject with, say, a texture gradient on a vertical or horizontal surface and having him match its apparent slant with an adjustable tilting rod (Clark, Smith, & Rabe, 1956), or compare it with the apparent slant of a neighboring textured surface (Phillips, 1970). Alternatively, the subject may be asked to set a marker at the apparent midpoint of such a gradient (Newman, 1971). It could be argued that some of these tasks have intellectual, memory, or motor components which make them less than ideal measures of the subject's immediate percept.…”
Section: Methodsmentioning
confidence: 99%